Inspeção visual automática de grãos agrícolas: demandas, potenciais aplicações e desafios para transferência de tecnologia no setor agrícola - Gomes, Robson Aparecido (2024)
Technologies for automatic visual inspection of agricultural grains (IVAGA), in general, are used to analyze grain samples in order to classify them and identify defects. The growing global demand for agricultural grains and the search for efficiency in production processes have driven scientific research on these technologies. However, despite the growing number of studies, especially in the last decade, few discuss the application of these technologies in the agroindustry. Furthermore, the bibliographic survey conducted, which involved 137 works in the literature, revealed that none of them addressed technology transfer. Thus, important knowledge gaps still persist in this field. One of them is the lack of understanding of researchers' motivations for proposing technologies. Another limitation lies in the large-scale practical implementation of the technological solutions proposed in the literature, leading to a mismatch between scientific advances and their large-scale application in the agricultural sector. Thus, this research aimed to investigate the motivations for proposing IVAGA technologies, their relationship with the demands of the agricultural sector and the factors that hinder the transfer of these technologies to the agroindustry. To this end, the following qualitative and quantitative methods were used: bibliometric review, systematic literature review, and a survey to collect data on knowledge and use of IVAGA technologies, and on the challenges and barriers to technology transfer in the agricultural sector. The research showed that most of the IVAGA solutions proposed in the literature have low technological maturity, requiring adaptations to real environments. It also showed that the main barriers to the large-scale application of these technological solutions are the lack of dissemination of scientific knowledge, the need for qualified labor, high costs and resistance to changes in processes. Despite this, the literature highlights benefits such as automation, efficiency and loss reduction, evidencing a great potential of IVAGA technologies for modernizing the agricultural sector.